A minimally invasive approach to spleen histopathology in dogs: A new method for follow-up studies of spleen changes in the course of Leishmania infantum infection. (October 2016) - Santos, Silvana Ornelas; Fontes, Jonathan L.M.; Laranjeira, Daniela F.; Vassallo, José; Barrouin-Melo, Stella Maria; dos-Santos, Washington L.C.
Graphical abstract: Highlights: A minimally-invasive technique is proposed for studying spleen histology in dogs. Changes in structure and cell composition of spleen compartments can be studied. Pathological structures, such as granulomas, can be identified. Follow-up studies of the spleen in visceral leishmaniosis can be performed. Abstract: Severe forms of zoonotic visceral leishmaniosis (ZVL) are associated with disruption of the spleen structure. However, the study of spleen histology requires splenectomy or necropsy. In this work, we present a minimally invasive cell-block technique for studying spleen tissue histology in dogs with ZVL. We examined 13 dogs with and seven dogs without Leishmania infantum infection. The dogs with Leishmania infection had a lower frequency of lymphoid follicles (2/13, Fisher's test, P < 0.02) and a higher density of plasma cells (score 3, Fisher's test, P < 0.02) than uninfected dogs (5/7 exhibiting lymphoid follicles and a plasma cell score of 1). The dogs with Leishmania infection also presented with granulomas (8/13) and infected macrophages (5/13). These differences in the histological presentations of spleen tissue from infected and uninfected dogs corresponded to changes observed in conventional histology. Hence, the cell-block technique described here may be used in the follow-up care and study of dogs with ZVL and other diseases in both clinical practice and research.